Penerapan Model Pembelajaran Menyimak Komprehensif dan Kritis melalui Media Interaktif pada Mahasiswa - Abdulloh, Abdulloh; Surastina; Sudarmaji; Tio Pani (Lentera: Jurnal Ilmiah Kependidikan, 2024)
The problems raised in this research are based on problems that emerged after the listening activity, where only four to five students actively participated in the discussion, while the others tended to be passive and did not express opinions. The listening process requires full concentration from students. Therefore, it is necessary to apply innovative learning models by lecturers to improve the quality of the learning process. The author will use a qualitative descriptive method. The data source in this research came from second semester students of the Indonesian language and literature education study program. Data collection techniques used include observation, recording techniques, and unstructured interviews. Data analysis in this research generally includes several stages, namely: checking, organizing and coding. The aim of this research is to identify and analyze the use of interactive audio-visual media in learning comprehensive and critical listening skills in the Indonesian language and literature education study program STKIP PGRI Bandar Lampung. This research aims to explain the types of interactive audio-visual media used by lecturers, as well as how this media helps in delivering material and improving students' comprehensive and critical listening skills. In addition, this research assesses the effectiveness of using audio-visual media compared to traditional learning methods such as discussions and lectures. This research also identifies supporting factors that increase the effectiveness of learning critical listening skills through the use of multimedia, as well as revealing the obstacles faced in using laboratory equipment and audio-visual media during the learning process.